Islam Nusantara sebagai Strategi Penguatan Moderasi Beragama dalam Perspektif KH. Abdurrahman Wahid - Nadiatus Saadah; Muh. Akbar Mahdi Supriyanto (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
This study examines the views of KH. Abdurrahman Wahid (Gus Dur) on Nusantara Islam as a means of strengthening religious moderation in Indonesia. The background to this study is the rise of radicalism and exclusivism in religion, which necessitates an understanding of Islam that is tolerant, peaceful, and in harmony with local culture. This study employs a descriptive qualitative approach using a literature review method, and obtains primary data from Gus Dur’s works and secondary data from various relevant literature. The analysis process was conducted using content analysis to identify the values, principles, and practices of religious moderation. The results indicate that, according to Gus Dur, Islam Nusantara emphasizes a balance between universal Islamic values and local social and cultural conditions, humanistic and critical education, interfaith and intercultural dialogue, the empowerment of local wisdom, and exemplary conduct in social and political spheres. This strategy can strengthen tolerance, inclusivity, and social harmony, making Islam a humanistic, moderate religion that is in harmony with local conditions. Gus Dur’s thought is regarded as a model of contextual and relevant Islam for addressing the dynamics of a pluralistic society, as well as for strengthening peace and a socially just Islamic civilization.